Place of sanctuary: an appreciative inquiry approach to discovering how communities support breastfeeding and parenting - Virginia Schmied; Elaine Burns; Athena Sheehan (BMC, 2019)
Abstract Background Significant efforts by governments at a global and national level have not resulted in a significant increase in the duration of breastfeeding to six months. The views of family and social networks, and community attitudes particularly around breastfeeding in public, influence infant feeding decisions. Yet many interventions designed to increase breastfeeding focus on the individual woman and have not been developed from the 'ground up' in consultation with women and communities. This study aimed to identify the key components of Mother Infant Caring Communities that promote and support breastfeeding and early parenting. Methods Appreciative Inquiry was used to facilitate a 'Community Conversation' workshop in two local councils in Australia. Thirty-five participants attended the community conversation workshops including new parents, grandparents, children's services, local government, and representatives from maternity and child health services. In addition, one focus group discussion was conducted with six retail business owners or managers. Qualitative content analysis was used to analyse data. This paper presents the findings of the first phase (the Discovery phase) of the study. Results Four major themes emerged: "PLACE - A community for everyone"; "A PLACE for children and families"; "Sometimes a PLACE to breastfeed" and "The parent room: a hidden and unsafe PLACE to breastfeed". Participants described the characteristics of communities that provided a sanctuary and fostered well-being for parents and infants including, open green spaces, safe playgrounds, walking tracks and community hubs. Shopping centres were described as having the potential to be the 'village'. Community-based services to support breastfeeding and parenting were highly valued. Yet in both sites, participants stated that breastfeeding was rarely observed in public and bottle feeding was more evident. Conclusion Breastfeeding and parenting are embedded in the places where women and families live. Community spaces including shopping centres, should be designed to include infants and young children and offer appropriate facilities such as safe and clean parenting rooms. Health services must work with local government, businesses, and diverse community members to identify what parents' value about their community and design and implement innovative local strategies to support breastfeeding.